Effect of Myrtle (Myrtus communis) Extracts on Storage Stability of Chicken Frankfurters - Amensour, Mahassine; Sendra, Esther; Pérez-Alvarez, José Ángel; Abrini, Jamal; Fernández-López, Juana Fern (International Journal of Biotechnology for Wellness Industries, 2015)
The antioxidant and antimicrobial effects of water myrtle extracts (0.25 and 0.50%) were investigated against lipid oxidation (tiobarbituric acid reactive substances – TBARS) and microbial growth in vacuum-packed chicken frankfurters stored at 4±1ºC for 35 days. The effects of this extract on compositional, physicho-chemical and sensory characteristics of chicken frankfurters were also determined. Results showed that water myrtle extracts possess antioxidant (lower TBARS values that remained stable during the 35 days of storage) and antimicrobial properties (lower aerobic plate count) that may make them useful in the food industry. The addition of water myrtle extracts to frankfurters increased red/green and yellow/blue coordinates and decreased lightness values, which could indicate that Myrtus comunnis extract can also acts as a colorant in this type of meat products. Frankfurters with water myrtle extracts were scored similar to controls for overall appearance.